1992
DOI: 10.1143/jjap.31.l890
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity and ESR Spectrum of Buckminsterfullerene-Doped Poly(3-alkylthiophene)

Abstract: Buckminsterfullerene (C60) is effectively doped in poly(3-alkylthiophene). However, the characteristics of C60-doped poly(3-alkylthiophene) are different from the typical behavior observed in the case of conventional dopants. Electrical conductivity of poly(3-alkylthiophene) increases upon C60 doping and decreases again at higher concentration of C60. Its temperature dependence is also anomalous. The absorption spectrum changes markedly upon C60 doping. ESR linewidth decreases from 7.1 G to 1.9 G upon C60 dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…2, the PL intensity of PAT-6 at 710 nm was linearly quenched by La@C 82 doping up to more than 0.1 mol%. Although the data on the highconcentration doping with La@C 82 was not obtained at this stage, it is noted that these results were in agreement with the reported results for other fullerenes, 10) such as C 60 and C 70 with regard to the low-concentration doping. From the results of PL quenching, it is considered that the doping effects of metallofullerenes can be expected for photovoltaic applications and also that metallofullerenes must be efficient dopants for enhancing the photoconductivity of PAT-6.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…2, the PL intensity of PAT-6 at 710 nm was linearly quenched by La@C 82 doping up to more than 0.1 mol%. Although the data on the highconcentration doping with La@C 82 was not obtained at this stage, it is noted that these results were in agreement with the reported results for other fullerenes, 10) such as C 60 and C 70 with regard to the low-concentration doping. From the results of PL quenching, it is considered that the doping effects of metallofullerenes can be expected for photovoltaic applications and also that metallofullerenes must be efficient dopants for enhancing the photoconductivity of PAT-6.…”
supporting
confidence: 87%
“…10) In the case of PAT-6 films doped with La@C 82 at various concentrations of up to 0.1 mol%, the change of the absorption spectra is negligible and the absorption peaks coincided with that of the PAT-6 film. It is considered, therefore, that the charge transfer between PAT-6 and La@C 82 in the ground state hardly occurred at such dopant densities.…”
mentioning
confidence: 85%
“…2. The peak energy of the absorption spectrum is slightly lower than that of regiorandom poly(3-hexylthiophene)/C 60 composite (C 60 : 5 mol%) [25]. The photoconductivity of the PAT/C 60 composites is remarkably enhanced upon C 60 doping at around 1.8 eV, as pointed out above.…”
Section: Resultsmentioning
confidence: 65%
“…We also found that increasing the length of a side chain in PAT one may controll the GS CT, i.e. in polyoctadecilthiophene GS CT is not found 9 Earlier it was suggested that twists and bends of PAT chains due to disorder in side chains may rise the bottom of valence band in some parts of POT and make ground state CT eneigetically favourable if stabilised by self trapping effects in CP and C60 and Coulomb attraction 6 71hus new featuies can inlluerice the CT processes and we discuss below soiiie of this micioscopic processes. 1 Iowevei at the present stage mhen no analytical niotlels (like TLNl for CP) ale available for S1 states on (-'ti0 this aiialysis can be done only eithci-on the qualitative level or within sirnple a i d ically soluhle niodels.…”
Section: --mentioning
confidence: 80%